Gamifikasi dalam Bahasa Inggris: Menjelajahi Penggunaan Strategi Gamifikasi untuk Meningkatkan Motivasi dan Keterlibatan Siswa - Hardianti Hardianti (Neolectura, 2024)
Many students experience a lack of motivation and engagement in learning due to the monotonous learning system. Therefore, many teachers apply gamification strategies to increase student motivation and engagement in learning. This study investigates the integration of gamification strategies within English as a Foreign Language (EFL) instruction to amplify student motivation and engagement. Gamification, a methodology applying gaming elements in a non-game context, serves as a focal point to enhance learning participation and motivation. In the realm of EFL education, student motivation and engagement often pose significant challenges. Through qualitative methodology involving classroom observations, questionnaires, student interviews, and teacher reflections, this research assesses the impact of implementing game elements like point-based assessments, competitive dynamics, challenges, and rewards on student motivation and engagement in learning English. The findings underscore a notable surge in student motivation attributed to the incorporation of game elements, fostering a more enjoyable and competitive learning environment that encourages active student participation. This research contributes vital insight for educators, highlighting the efficacy of gamification as a tool to heighten motivation and engagement in EFL education. It emphasizes the need for judicious integration of relevant gaming elements in pedagogical design to craft more immersive and meaningful learning experiences for students studying English as a Foreign Language.